Navigating the complex terrain of motivated behavior: a bibliometric and neuroscientific perspective - Helou, Ammir Y.; Bittencourt, Jackson C. (Frontiers in Behavioral Neuroscience, 2024)
Over several decades, motivated behavior has emerged as a crucial study area within neuroscience.Understanding the neural substrates and mechanisms driving behaviors related to reward, addiction, and other motivation forms is pivotal for novel therapeutic interventions. This review provides a bibliometric analysis of the literature, highlighting the main trends, influential authors, and the potential future direction of the field.Utilizing a dataset comprised by 3150 publications from the Web of Science and Scopus databases ("motivated behavior as query), we delve into key metrics like publication trends, keyword prevalence, author collaborations, citation impacts, and employed an unsupervised natural language processing technique -Latent Dirichlet Allocation -for topic modeling. From early investigations focusing on basic neural mechanism and behaviors in animal models to more recent studies exploring the complex interplay of neurobiological, psychological, and social factors in humans, the field had undergone a remarkable transformation. The last century has seen a proliferation of research dedicated to uncovering the intricacies of motivation, significantly enriching our understanding of its myriad implications for human behavior and mental health. This bibliometric analysis aims to offer comprehensive insights into this dynamic research area, highlighting the field's key contributions and potential future directions, thereby serving as a valuable resource for researchers, and hopefully give a more thorough understanding of the research area.